The importance of financial analysis in enhancing the quality of financial reports of commercial banks listed on the Palestine Exchange - a field study - Mohamed altaweel, Issam (Journal of Research in Finance and Accounting, 2024)
The study aims to determine the importance of financial analysis in enhancing the quality of financial reports. The study population was selected from commercial banks listed on the Palestine Stock Exchange, and a random sample of 106 participants was chosen, including branch managers, department heads, and accountants. A questionnaire was used as a data collection tool, employing a descriptive analytical approach. The results showed that the percentage of the importance of financial analysis in enhancing the quality of financial reports for commercial banks listed on the Palestine Stock Exchange reached 85.2%, which is a very high percentage. Financial analysis contributes to making financial reports more suitable for decision-making, and financial information based on financial analysis provides high reliability in financial reports. The main recommendations include the necessity of implementing financial analysis to reduce the likelihood of uncertainties in financial reports and support their suitability and effectiveness. It is also important to enhance financial analysis based on appropriate, reliable, and up-to-date accounting information to improve the quality of financial reports. Furthermore, it is essential to present financial information based on financial analysis in a manner that accurately reflects financial transactions and other relevant events.